Recovery of iron and lead from a secondary lead smelter matte by magnetic separation. (15th June 2018) - Kukurugya, Frantisek; Rahfeld, Anne; Möckel, Robert; Nielsen, Peter; Horckmans, Liesbeth; Spooren, Jeroen; Broos, Kris
Highlights: A mineral process based on magnetic separation and oxidizing roasting is proposed. The Fe content in matte was increased from 49 to 61 wt%. FeS was transformed to Fe2 O3 by oxidizing roasting. MLA analysis gave detailed insights in the magnetic separation process. Behavior of Pb during LIMS depends on the particle size and thus its liberation. Abstract: A secondary Pb smelter matte with a total Fe grade of ca. 50% (as FeS, Fe3 O4, FeO and metallic Fe), shows good potential for being used as a secondary Fe source. However, requirements for Fe ore are: a total Fe grade >60% and a sulphur content as low as possible. Therefore, further treatment steps are necessary to increase the Fe content in the matte. Dry low intensity, wet low intensity and wet high intensity magnetic separation experiments were performed on different particle size fractions of the matte. Mineral liberation analysis (MLA) was performed to explain different behaviours of Pb in the different size fractions during magnetic separation. Moreover, oxidizing roasting at 600 °C was carried out to transform FeS to Fe2 O3, which is the more prefered form of Fe for pig iron production. Results show that by combining low and high intensity magnetic separation and oxidizing roasting, material with a total Fe grade of 61% (as oxide) can be recovered in the magnetic fraction representing circa 50% of the initial weight of the sample. Moreover, the sulphur content was reduced from initial 20 to 4% in the final magnetic fraction. Further reduction in sulphur content would require an additional desulphurization step.